Department of Communication and Marketing - (:unkn) unknown (My University, 2026)
The Department of Communication and Marketing at the Cyprus University of Technology aspires to establish itself as a regional center for teaching and research in the field of public communication and to gradually become a nationally and internationally recognized center of excellence. Its mission is to enhance scholarship in the field of public communication, predominantly in those aspects that are linked to the media, journalism, political communication, advertising and public relations. It will strongly focus on the European dimension and on the related domains of the communicative disciplines, with emphasis on the historical, social and political aspects of their evolution.